Cyberlindnera jadinii (teleomorph Candida utilis) candidaemia in a patient with aplastic anaemia: a case report. (10th July 2018) - Treguier, Pauline; David, Marion; Gargala, Gilles; Camus, Vincent; Stamatoullas, Aspasia; Menard, Anne-Lise; Lenain, Pascal; Contentin, Nathalie; Lemasle, Emilie; Lanic, Helene; Tilly, Hervé; Jardin, Fabrice; et al.
Abstract : Introduction. We present what is believed to be the first report of candidaemia caused by Cyberlindnera ( Pichia ) jadinii (teleomorph of Candida utilis ) in a patient with an aplastic anaemia. Case presentation. The patient, a 21-year-old male, presented with hepatic cytolysis, cutaneous and pulmonary involvement, and septic shock. Cyberlindnera jadinii was identified by aerobic blood culture and MS. The patient initially received multiple and combined antifungal therapy, but continued to have persistent skin lesions and fever. He was successfully treated by emergency haploidentical haematopoietic stem cell transplantation, combined with triple antifungal therapy and supportive care. Conclusion. Cyberlindnera jadinii, teleomorph of Candida utilis, which is not usually invasive, can lead to an opportunistic invasive infection in unhealthy adult patients. For treatment of the invasive candida infection, it is necessary to combine antifungal therapy and supportive care.